Consumer Ethnocentrism and its Impact on Purchase Intention of Foreign Apparel Brands: Moderating Effect of Demographics - Shreya Gupta, (International Journal of Engineering and Management Research, 2024)
The main purpose of this study is to examine the level of consumer ethnocentrism i.e. to check for the presence of ethnocentrism among Indian consumers based on the foundation of the social identity theory, and to see if the ethnocentrism level varies across the demographic variables of gender, age, education and income levels. The study also aims to analyse the impact of ethnocentrism on the purchase intention of foreign apparel brands, along with analysing the impact of demographics as moderator variables in the relationship between consumer ethnocentrism and purchase intention of foreign apparel brands. The results indicated an overall existence of ethnocentrism among the respondents. The ethnocentrism level across the demographics showed that such levels varied across gender, education, and income but did not vary with regard to the age of the respondents. A significant negative relationship was found between consumer ethnocentrism and purchase intention of foreign apparel brands, with no demographic variable serving as a moderator in this relationship.